DAKWAH DALAM TRADISI AKADEMIK DAN STUDI ISLAM - EKO NOPRIYANSA (Jurnal khabar: Komunikasi dan Penyiaran Islam, 2020)
The success of the leaders of the spread of Islam in the past, has made Indonesia as the largest Muslim population in the world without leaving a historical trail of warfare and violence, so that in its development, Indonesia's strategic role in tackling various social and humanitarian problems, has displayed a face of wisdom and sought to show to the world of their maturity in exposing the plurality and diversity of the population, which is within the territory of the Unitary Republic of Indonesia. Furthermore, no less interesting, even though Indonesia is dominated by Muslims as a majority, Indonesia is not a country that claims a religion, but the Indonesian people recognize their identity as the Pancasilalis people. In this research is an effort to see globally the application of da'wah in Cross-Asia both regarding Models, Implementation, Theory, to various academic phenomena of Islamic Leaders across Asia in exposing Da'wah as a discipline of Science or as a belief in totality in Islam, so that really can find various patterns and social relevance about how the implementation of Da'wah in various regions, both as an academic discipline, as well as subjective beliefs. So that in the end, it can encourage practitioners and propaganda activists to synchronize the implementation of their da'wah with the science methodology, so that the Da'wah process without reaping significant obstacles in the midst of a social society that is Plural and full of diversity.,